Pengaruh Literasi Keuangan terhadap Kinerja Usaha UMKM di Desa Palem Watu, Kecamatan Menganti, Kabupaten Gresik - Fasya Raihan Anwar, Redhinta; Vira Angelina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the effect of financial literacy on MSME business performance in Palem Watu Village, Menganti Sub-district, Gresik Regency. Financial literacy, which includes understanding and ability to manage finances, is expected to contribute positively to the business performance of MSME actors. The research method used is a quantitative approach using a simple linear regression test analysis method. The data obtained are MSMEs in Palem Watu Village. The results of this study indicate that financial literacy has a significant effect on the performance of MSMEs. The results of the coefficient of determination analysis show an r square value of 65.2%, while the remaining 13.7% is influenced or caused by other factors not included in the study.